PENERAPAN METODE KOOPERATIF TIPE JIGSAW TERHADAP PENINGKATAN HASIL BELAJAR MUATAN LOKAL (BAHASA MADURA) SISWA KELAS VI DI UPTD SDN BANYUAJUH 5 - Titin Fatinah; Agung Setyawan (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
This study aims to analyze logical-mathematical intelligence in problem-solving in terms of adversity quotient. This research is a qualitative descriptive study. The research subjects were fifth-semester students of the Tarbiyah Faculty, Ibrahimy University. Data collection techniques using questionnaires, tests, and interviews. The questionnaire was conducted using a Likert adversity quotient scale. The results of the Likert adversity quotient scale analysis of students are grouped into 3 categories, namely: quitter, camper, and climber. Tests in the form of problem-solving questions were carried out to measure students' logical-mathematical intelligence. Interviews were conducted with 6 students based on the adversity quotient category and level of ability on the test results. Data analysis was carried out in a qualitative descriptive manner, in the form of a theory of induction and data reduction. The results of the research based on the adversity quotient category and ability test results show that: 1) In the quitter category, there are 3 students with low ability (10%). 2) In the camper category, there are 2 students with low ability (6.7%), 10 students with medium ability (33.3%), and 3 students with high ability (10%). 3) In The climber category, there are 6 students with moderate abilities (20%) and 6 students with high abilities (20%).